Dispensing of antibiotics without prescription in the metropolitan area of Athens, Greece, in 2021—Can new legislation change old habits?. Issue 1 (2nd March 2023) - Kopsidas, Ioannis; Kokkinidou, Lydia; Petsiou, Dioni Pinelopi; Kourkouni, Eleni; Triantafyllou, Christos; Tsopela, Grammatiki-Christina; Zaoutis, Theoklis
Abstract: Objective: To assess the effect of new legislation on the dispensing of antimicrobials without prescription from pharmacies in Greece. Design: In-person survey. Setting: The study included 110 pharmacies in the greater Athens Metropolitan area. Methods: Volunteer collaborators visited 110 pharmacies in the greater Athens Metropolitan area in December 2021 and January 2022. They asked for either ciprofloxacin or amoxicillin-clavulanate acid (6:5 ratio) without providing a prescription, without simulating symptoms, and without offering justification or insisting. Fluoroquinolones have additional dispensing restrictions in Greece. Results were compared to a 2008 study. In 2020, legislation allowed the dispensing of antibiotics from pharmacies only with an electronic prescription, overriding the 1973 forbidding the dispensing of all medications without prescriptions. Results: All pharmacists refused to dispense ciprofloxacin without a prescription. Only 1 pharmacy dispensed amoxicillin-clavulanate without a prescription. Compared to the 2008 study, dispensing of amoxicillin-clavulanate without a prescription dropped from 100% in 2008 to 1% in 2021 and dispensing ciprofloxacin without a prescription dropped from 53% in 2008 to 0% in 2021. Conclusions: A new and enforced law that requires electronic prescribing led to a dramatic reduction of antibiotic dispensing without prescription compared to 12 years ago. Similar initiatives could help solve the problem of antibiotic consumption and resistance in Greece and elsewhere.